2021
DOI: 10.1590/0034-7167-2021-0061
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unprotected sex in people who consume sexually explicit media

Abstract: Objective: To analyze the factors associated with sex without the use of condoms in consumers of sexually explicit media (SEM). Methods: Cross-sectional study, with a sample of 172 participants selected and collected through social media. To assess the predictors of unprotected sexual practices, the Poisson regression model was used. Values were expressed as a robust prevalence ratio (PR) with their respective confidence intervals. Results: There was a statistically significant association between, the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
4
0
4
Order By: Relevance
“…It has been observed that traditional forms of sex education involving interaction with educators have been the participants’ least used sources, with the use of impersonal sources, such as pornography, the internet and social networks, growing exponentially. Other studies have also shown that adolescents and young people prefer anonymity, not only for education but also for personal interactions [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that traditional forms of sex education involving interaction with educators have been the participants’ least used sources, with the use of impersonal sources, such as pornography, the internet and social networks, growing exponentially. Other studies have also shown that adolescents and young people prefer anonymity, not only for education but also for personal interactions [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been observed that viewing pornography as a source of education is related to adolescents and young people attitude towards contraceptive use during both their first relationship and during their last coital relationship before taking the questionnaire. Thus, we can see how young people who were educated through pornography were those who used the withdrawal method to a greater extent or used no method, and when they did use a condom, it was only for the moment before ejaculation with no protection used for foreplay [ 14 , 20 , 32 , 34 ]. Those who received educational talks are the best protected, not only against pregnancy, but also against sexually transmitted diseases as they used condoms and hormonal contraception, a fact observed internationally [ 13 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A baixa renda é fator que influencia o acesso à pornografia virtual, pois precisa investir em dispositivos eletrônicos. Esse achado diverge de outro estudo on-line realizado no Brasil, em que se constatou renda média dos participantes superior ao salário-mínimo brasileiro, o que facilita a conectividade via internet, o uso de celulares e computadores e, assim, o consumo de mídias sexuais (11) . No entanto, é importante salientar que, atualmente, a internet permeia todas as classes sociais, ou seja, todos podem ter acesso a esse tipo de mídia.…”
Section: Discussionunclassified
“…Estudo on-line, realizado no Brasil, que levantou fatores associados ao sexo sem uso de preservativos por pessoas consumidoras de MSE identificou que o consumo está associado à prática sexual sem uso do preservativo, sendo que preferir cenas de sexo sem uso de preservativos aumentou a chance de sexo sem preservativos, na amostra de estudo, em mais de quatro vezes (19) . Além disso, no presente estudo, essa prática de risco pode ser explicada pelas características sociais da amostra, como a faixa etária jovem, que costuma ser associada ao sexo desprotegido (11) , e conhecimento frágil sobre IST (20) .…”
Section: Discussionunclassified